A violência contra a mulher: o estupro marital - Silva, Jocélia Alves da (Fundação Universidade Federal do Tocantins, 2025)
Despite advances in society in favor of rights, including those aimed at women, as seen in the creation of the Maria da Penha Law in 2006, the growth in the number of cases of rape and marital violence continues to grow over the years, in the country. The present investigation sought to characterize women victims of marital rape in the city of Araguaína, in the state of Tocantins (TO), presenting reflections, based on reports and data made available by the Police Station Specialized in Women's Assistance (DEAM) and the Reference Center Specialized Social Assistance (CREAS), promoting an understanding of the reality experienced by women, analyzing the historical and cultural factors that underpin society in the region. The general objective of the research was to verify which factors present in society were capable of explaining marital rape. As specific objectives, the following were listed: conceptualizing marital rape, identifying the possible factors that favor marital rape and understanding how women perceive the issue of marital rape in today's society. The research aimed to answer the following question: what historical and social factors explain marital rape and its naturalization in society today? Thus, the study investigated the characteristic complex of marital violence based mainly on data obtained through interviews carried out with women victims of sexual violence and marital rape. In its methodological approach, the research was constructed as a qualitative work, based on a documentary and bibliographical analysis. WebQDA software was used to support the analyses. The data were analyzed from the perspective of dialectical historical materialism and in light of concepts from the theoretical framework of recent feminist literature. The justification for developing this study arose from my work in Social Services, as I carry out work activities directly with women who are victims of violence. Based on the conceptual considerations constructed and the analysis developed, it was concluded that the probability of a woman being a victim of conjugal violence increases in relation to the following indicators: situation of economic insecurity, mental health of the victim, lack of psychological support, social and emotional resources, and perpetuation of violent acts within the couple's relationship.